2015
DOI: 10.3109/14767058.2014.987748
|View full text |Cite
|
Sign up to set email alerts
|

Fetal exposures and perinatal influences on the stool microbiota of premature infants

Abstract: Objective To test the hypothesis that maternal complications significantly affect gut colonization patterns in very low birth weight infants. Methods 49 serial stool samples were obtained weekly from 9 extremely premature infants enrolled in a prospective longitudinal study. Sequencing of the bacterial 16S rRNA gene from stool samples was performed to approximate the intestinal microbiome. Linear mixed effects models were used to evaluate relationships between perinatal complications and intestinal microbiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 30 publications
1
61
0
Order By: Relevance
“…This finding is similar to those of previous studies focused on the use of maternal antibiotics in general, particularly with the decrease in Bacteroides and Bifidobacterium. [38][39][40][41][42][43]46,47 One study 40 observed significant effects of GBS prophylaxis on the infant gut microbiome at 6 months among 150 pregnancies for members of Clostridiaceae, Ruminococcoceae and Enterococcaceae whereas another 41 (n = 83) found lower levels of Bifidobacterium and Escherichia at 12 weeks of life in infants of mothers exposed to intrapartum antibiotics.…”
Section: Main Findingsmentioning
confidence: 99%
“…This finding is similar to those of previous studies focused on the use of maternal antibiotics in general, particularly with the decrease in Bacteroides and Bifidobacterium. [38][39][40][41][42][43]46,47 One study 40 observed significant effects of GBS prophylaxis on the infant gut microbiome at 6 months among 150 pregnancies for members of Clostridiaceae, Ruminococcoceae and Enterococcaceae whereas another 41 (n = 83) found lower levels of Bifidobacterium and Escherichia at 12 weeks of life in infants of mothers exposed to intrapartum antibiotics.…”
Section: Main Findingsmentioning
confidence: 99%
“…Such fetuses are thus exposed to sources of potentially virulent microbes. Exposure to these insults leads to a less diverse infant gut microbiome, with relatively higher numbers of pathogenic bacteria being present (Chernikova et al, ). Infections during pregnancy are well known to interrupt normal gestation by both altering the vaginal flora as in bacterial vaginosis, or by increasing susceptibilities for other infections that could alter both maternal and infant microbiomes (Redelinghuys et al, ).…”
Section: Part Imentioning
confidence: 99%
“…In recent years, the long-held theory that the womb is sterile has been met with an increasing body of evidence to the contrary. Numerous 16S rDNA next-generation sequencing (NGS) studies have reported on a fetal gut microbiome (Mshvildadze et al 2010;Gosalbes et al 2013;Hu et al 2013;Moles et al 2013;Ardissone et al 2014;Del Chierico et al 2015;Hansen et al 2015;Chernikova et al 2016;Collado et al 2016;Wampach et al 2017). However, while these studies have detected bacterial DNA in the fetal gut, they have not been able to provide information on whether this DNA comes from viable organisms.…”
Section: Introductionmentioning
confidence: 99%